The Green Scepticism Paradox: How Green Marketing Drives Willingness to Pay More Through Brand Image in Hospitality - Pitaswari, Ni Made Pinkan; Kusuma, Agung Artha (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Growing environmental awareness has encouraged companies to adopt green marketing strategies to attract more conscious consumers and increase their willingness to pay. However, green scepticism persists even when a brand has a strong green image, meaning that consumers may continue to question the credibility of environmental claims despite positive brand perceptions. Purpose: This study examines how green marketing influences willingness to pay more through green brand image, with green scepticism acting as a moderating variable among Millennials and Gen Z. Design/methodology/approach: This study employed a quantitative approach using purposive non-probability sampling. Data were collected from 245 Millennials and Gen Z consumers engaged with sustainable hospitality in Indonesia and analysed using SEM-PLS with a moderated mediation approach. Findings/Result: Green marketing significantly strengthens green brand image, which subsequently increases willingness to pay more. Green brand image also mediates the relationship between green marketing and willingness to pay more. However, green scepticism does not significantly moderate the relationship. Conclusion: The study reveals that a strong green brand image directly drives consumers’ willingness to pay more by fostering long-term commitment. Furthermore, green scepticism fails to weaken this relationship, proving that established brand trust allows positive purchasing behavior to persist despite general consumer doubts. Originality/value (State of the art): This study addresses a key literature gap by applying the Stimulus-Organism-Response framework to green marketing, a methodology that has not yet been sufficiently utilized to examine how green marketing forces shape consumer attitudes and behaviors toward sustainable brands. It extends sustainable hospitality research by evaluating willingness to pay more through green brand image and green scepticism in the Indonesian context. Keywords: green marketing, green brand image, green scepticism, willingness to pay more, sustainable consumer behavior